Effect of Carbonization Time of Mesoporous Carbon in the Dyes Adsorption: Rhodamine B, Methylene Blue and Carmine - Misriyani Misriyani; Tutik Setianingsih; Darjito Darjito (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Study of dyes adsorption (rhodamine B, methylene blue and carmine) by using mesoporous carbon synthesized at various carbonization time has been done. Purpose of this research was to understand influence of carbonization time to performance of the mesoporous carbon in dyes adsorption. In addition, adsorption performance of the mesoporous carbon and commercial carbon were compared. The adsorption test were conducted at conditions: 0.1 g of adsorbent, 25 mL of dyes solutions 100 ppm and shaking rate 125 rpm for 4 hour. Filtrate was used to determine remain concentration of the dyes with UV-visible spectrophotometry. Result of the research showed that the carbonization time from 1 to 3 hours improved the adsorption, whereas from 3 to 5 hours decreased it. The best character of the mesoporous carbon was obtained at carbonization time of 3 hours with adsorption values of 96.43 ± 0.37 % for rhodamine-B, 38.80 ± 1.44 % for methylene blue and 48.51 ± 1.55 % for carmine. The adsorption values of the mesoporous carbon were 0.97 times for rhodamine B, 0.48 times for carmine, and 0.39 times for methylene blue compared with the commercial activated carbon.